2019
DOI: 10.21037/tcr.2019.08.42
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the time from the completion of neoadjuvant chemotherapy to surgery on the outcomes of patients with gastric cancer

Abstract: Background: Gastrectomy is usually recommended within 5 to 6 weeks after the completion of neoadjuvant chemotherapy (NCT). However, the optimal timing of surgery is not clearly defined.Methods: This study retrospectively reviewed the clinical records of 229 patients with locally advanced gastric cancer (GC) who underwent curative gastrectomy after NCT between 2006 and 2016. The effect of the time to surgery (TTS), defined as ≤4, 5-6, and >6 weeks, on patient outcomes was examined. Descriptive statistics and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…In contrast to the findings of Liu et al (11), a relative short-term interval before surgery (3-5 weeks) was an independent protective factor for OS and PFS with no statistical pathologic improvement. Our results are contrary to previous findings relating to rectal and esophageal cancer, in which longer waiting time is believed to achieve a better pathological response (6,8,(28)(29)(30).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the findings of Liu et al (11), a relative short-term interval before surgery (3-5 weeks) was an independent protective factor for OS and PFS with no statistical pathologic improvement. Our results are contrary to previous findings relating to rectal and esophageal cancer, in which longer waiting time is believed to achieve a better pathological response (6,8,(28)(29)(30).…”
Section: Discussioncontrasting
confidence: 99%
“…Time interval to surgery after the completion of NACT is a common question asked by patients with GC, but it is a question without a definite answer. There have only been a few retrospective studies on this topic with limited sample size, and these have come to different conclusions (10,11,25). Liu et al (10) first presented a retrospective study of 176 patients with GC and proposed that prolonged interval time of >6 weeks was associated with an increased rate of pCR but not with OS or DFS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The propensity score matching in this study was performed between high TTS patients and low TTS patients to eliminate the bias from the impact of this factor on survival. In addition, other studies suggested the most common factors for delayed operation included heavily economic level of patients, the management of health insurance, and the busy turnover of beds in hospital 36,37 …”
Section: Discussionmentioning
confidence: 99%